Effects of trehalose and dough additives incorporating enzymes on physical characteristics and sensory properties of frozen savory Danish dough. (December 2017) - Halagarda, Michał
Abstract: For economic reasons dough freezing technique is nowadays commonly employed in bakery business. There are, however, several issues connected with this technology. To improve the quality of a ready product, baked from frozen dough, some attempts concerning manipulation of production process parameters as well as supplementation of dough formulas with additives have been made. The aim of this study was to analyze the effects of various additives, including ready to use bakery products, on the crumb structure and specific volume of baked savory Danish dough. The research results show that by using most of the selected additives, an improvement of the volume and crumb structure of the product baked from frozen dough can be achieved. The only exception is the supplementation of the dough with 2% of trehalose. The most similar properties to the control sample, baked without the use of freezing technique, were observed in 3 formulas. One was made with the use of a commercial product, the second using fungal α-amylase, whereas the third - a blend of fungal α-amylase, glucose oxidase, fungal amyloglucosidase and enzymatic complex of lipases and xylanases. Nevertheless, an impact of these additives on the flavor profile of the dough was noted. Highlights: An impact of dough additives on the structure of savory Danish dough was checked The effects of dough supplementation with selected additives were compared An influence of additives on the flavor profile of the dough was verified Consumer acceptance of dough supplemented with selected additives was determined